Development of a customizable mouse backbone spectral flow cytometry panel to delineate immune cell populations in normal and tumor tissues - Longhini, Ana Leda F.; Fernández-Maestre, Inés; Kennedy, Margaret C.; Wereski, Matthew G.; Mowla, Shoron; Xiao, Wenbin; Lowe, Scott W.; Levine, Ross L.; Gardner, Rui (Frontiers in Immunology, 2024)
Introduction In vivo studies of cancer biology and assessment of therapeutic efficacy are critical to advancing cancer research and ultimately improving patient outcomes. Murine cancer models have proven to be an invaluable tool in pre-clinical studies. In this context, multi-parameter flow cytometry is a powerful method for elucidating the profile of immune cells within the tumor microenvironment and/or play a role in hematological diseases. However, designing an appropriate multi-parameter panel to comprehensively profile the increasing diversity of immune cells across different murine tissues can be extremely challenging. Methods To address this issue, we designed a panel with 13 fixed markers that define the major immune populations –referred to as the backbone panel– that can be profiled in different tissues but with the option to incorporate up to seven additional fluorochromes, including any marker specific to the study in question. Results This backbone panel maintains its resolution across different spectral flow cytometers and organs, both hematopoietic and non-hematopoietic, as well as tumors with complex immune microenvironments. Discussion Having a robust backbone that can be easily customized with pre-validated drop-in fluorochromes saves time and resources and brings consistency and standardization, making it a versatile solution for immuno-oncology researchers. In addition, the approach presented here can serve as a guide to develop similar types of customizable backbone panels for different research questions requiring high-parameter flow cytometry panels.